Multipolarity in plural: resignification(s), language games, and Russia's multiple identities - Makarychev, Andrey (2011)
Abstract: "In his working paper, the author addresses the situation of linguistic uncertainty that gives obvious political effects. He approaches the concept of multipolarity, which has been well-known for decades, and demonstrates that it has multiple meanings in Russia. He challenges the almost iconic uniformity of the idea of multipolarity, showing that it hides many alternative discourses, both academic and political. As a 'Russian doll', the unpacked multipolarity breaks down into a number of fragments, which constitute a certain menu of Russia's foreign policy choices. The author invites to think more creatively about Russian foreign policy narratives by asking such questions as: how 'real' is multipolarity in the eyes of Russian experts? Is there a gap between its academic understanding and political meaning? Shall Russia and EU find a common language in their worldviews, or are discursive disconnections between them to prevail?" (author's abstract)